Geographie und spatial turn - Lossau, Julia; Lippuner, Roland (ERDKUNDE, 2004)
Partly based in the discourse of globalisation, the social sciences are currently witnessing what is often referred to as the 'spatial turn'. After an extended episode of discursive exile, spatial categories of analysis are celebrating their return to the social-scientific agenda. This has led to a situation where German-speaking geography, a discipline which used to be of rather peripheral status for the larger part of the 20th century, finds itself standing at the heart of the prevailing debate. While geographers try to come to terms with the new significance of their discipline, the actuality of the spatial turn is hardly questioned. Against this atmosphere of general acceptance, if not affirmation, this paper aims at problematising the supposed evidence of the spatial turn, conceptualising it as the mere talk of the spatial turn. This talk, it is argued, is historically parochial since it implies that space has not been conceptually important before its revitalisation. Moreover it will be shown that in this talk, the social realm is more often than not projected onto and conflated with the physical world. How difficult indeed it is to avoid this theoretical lapse and keep the two realms separate from each other will be demonstrated using the pertinent work of PIERRE BOURDIEU. In order to avoid the related 'territorial trap', this paper finally sketches out ways of geographical analysis that move beyond essentialist concepts of space and place. In this respect, both post-colonial theory and systems theory seem to be possible signposts. By following these signposts, it is concluded, geographers would react more appropriately to the assumed 'revitalisation of space and place' than by unreflexively echoing the talk of the spatial turn.